PENGARUH ADANYA SANKSI DAN DENDA PERPAJAKAN DALAM ISLAM TERHADAP KEPATUHAN WAJIB PAJAK DI INDONESIA - Della Fadhilatunisa; Andika Isma; Dzakiyyah Alfaaizah; Haliana Halim; Muh. Yusuf K (Universitas Negeri Makassar, 2023)
Tax sanctions dan tax regulations are increasingly developing. Similarly, islamic law will develop according to the times. And of course the Ulama will study new phenomena based on islamic law, one of which is regarding taxes. In determining the law regarding taxes and their sunctions, there are differences of opinion among of scholars. Most of them forbid, and most of them allow it with some conditions. The results of this study indicate that sanctions and fines in Islam are allowed on condition that they are used for the benefit of the people, not for actions that are contrary to Islam such as disobedience. Sanctions and fines in taxes are determined jointly by deliberation by the representatives of the people, which means that their determination is in accordance with the principle of Equal Rida (Anta Radhin).